Students reflecting on test performance and feedback: An on-line approach - Fyfe, Georgina; Fyfe, Susan; Meyer, J.; Ziman, M.; Sanders, K.; Hill, J. (Routeledge, Taylor & Francis Group, 2013)
Undergraduate students accessing on-line tests in Human Biology in three Western Australian universities were asked to complete an on-line post-test reflective survey about their perceptions of their test performance in light of automated feedback. The survey allowed pre-determined choices and comment text boxes relating to students’ perceptions of their performance, self-identified areas of difficulty and suggested strategies for improving test performance. One-third of students undertaking on-line tests responded to the optional survey, and 60% of respondents thought reflecting on feedback was useful. Students reflecting on formative rather than summative assessment reported a more strategic approach to testing, often using it to assess their knowledge and prepare for future assessment. Their reflections were more internally focused on motivation and preparation compared with those assessed summatively. Respondents were more likely to be female, older, more experienced learners who hadscored well in the test. Younger respondents expected higher scores than they achieved and were less likely to reflect, but, when they did, were more likely to select pre-determined reasons for their performance and less likely to suggest strategies for improvement. These results support formal training and scaffolded integration of reflection into on-line assessment feedback, especially for less experience learners.